The phenomenon of commercial sex services through the MiChat application (A study on 3 female students of University X in Pekanbaru) - Abdul Munir; Saleh, Rachmat Fajar (Sisi Lain Realita, 2024)
This study examines the phenomenon of commercial sex service use through the MiChat application among students and workers in Pekanbaru. The issue focuses on the driving factors behind the use of such services, as well as the impacts on individuals and society. The objective of this research is to understand the motivations and the interaction process between service providers and clients, as well as to investigate the perspective of public administrators regarding this phenomenon. The research method employed is qualitative, with interviews conducted with informants, including service providers, clients, public complaint managers, and hotel employees. The findings reveal that loneliness, emotional needs, and the desire for exploration are the main reasons for using these services, while the transaction process typically involves clear communication and the selection of safe locations. Referring to Rational Choice Theory, which explains that individuals make decisions based on a cost-benefit analysis. The conclusion of this study is that this phenomenon reflects complex individual needs, while also highlighting the importance of awareness of the associated risks and the necessity for government and societal intervention to provide healthier alternatives.